The Effects of Internal Control Information Disclosure on Audit Fees in Chinese Market - Guo, Junjian (2019)
This paper mainly explores the association between internal control information disclosure (ICI) and audit fees in Chinese market. The indicators of ICI in this paper include the internal control audit report disclosure (ICA), inter control self-evaluation report disclosure (ICS), internal control deficiencies disclosure (ICD), internal control information deficiencies rectification (REC) and internal control complexity (REV). Combined with the background in China, and linked with agency theories, information theory, signaling theory and insurance theory, this paper proposes five hypotheses to examine whether there exists association between ICI and audit fees. Through selecting 2,391 Chinese listed companies as samples every year during 2014 to 2018, this paper chooses quantitative research method, designs two regression models and analyzes empirical results. Eventually, it could be concluded that ICA, ICD and REV are positively associated with audit fees, ICD and REC are negatively associated with audit fees.